Australian Institute of Sports Position Statement Supplements and Sports Foods in High Performance Sport (AIS, 2021)
Sports foods and supplements can play a small but important role in the sports nutrition plans of high performance athletes. Sporting organisations, sports science and medicine practitioners, coaches and athletes all contribute to a pragmatic and transparent approach that balances the pros and cons of supplement/sports food use by considering: is it safe? Is it effective? Is it permitted for use in sport?